Gains from Sharing: Sticky Norms, Endogenous Preferences, and the Economics of Shareable Goods - Anders Fremstad (University of Massachusetts, Department of Economics, 2014)
There are often "gains from sharing" underutilized goods with others. People routinely share tools, media, gear, electronics, toys, space, and vehicles with relatives, friends, and neighbors, and the internet is opening up new opportunities to share them with strangers. Drawing on the work of James Buchanan, Elinor Ostrom, and Yochai Benkler, I develop an economic framework of decentralized sharing. My analysis challenges the implications of simple economic models, which ignore the role of sticky norms and endogenous preferences and, therefore, suggest that people are always sharing at efficient levels. I argue that the online platforms may gradually transform norms and preferences to substantially increase peer-to-peer borrowing and lending. Using data from General Social Survey, the Consumer Expenditure Survey, the online platform NeighborGoods, and my own survey, I estimate the current and potential value of decentralized sharing. I find that today peer-to-peer borrowing is worth at least 179 a year for 30 percent of Americans and at least 774 for 8 percent of Americans. If the online platforms are able to facilitate high levels of sharing among loosely-tied individuals, the annual benefit to the average household would be modest but significant, perhaps one thousand dollars a year. My analysis suggests that that there are significant gains from sharing tools, media, gear, electronics, toys, pets, vacation homes, and lodging, but the largest gains will likely come from sharing privately-owned vehicles.
Keywords: D10; D70; Q01; 330; theory of clubs; theory of households; excludable non-rival goods; decentralized cooperation; reciprocity